Jihad dan Hukum Perang dalam Islam - Muflikhatul Khairah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
This article originates from the issue of jihad which becomes so distorted especially after 9/11 terrorist attack.Â It traces the concept of jihad in islam, the relationship between jihad and warfare or qitÄl fÄ« sabÄ«lillÄ«h, and application of jihad throughout Islamic history.Â This is a descriptive writing with content analysis and thematic interpretation of al-Qurâ€™an. It concludes that jihad is the ultimate effort done by Muslims to guard, protect, and defend their religion and the ummah. Warfare or qitÄl fÄ« sabÄ«lillÄ«h is a form of jihad with the purpose of defending and protecting the ummah from the menace of the enemies defensively as well as repressively. Warfare in Islam has philosophical aim of dafâ€˜ al-darar or preventing from harms which has to be executed with the principle of tadarruj or staging and priority.On that basis, warfare in Islam is not an act of expression for revenge which is done haphazardly, but it has to be rationally considered and calculated for its benefits and harms. Waging war unilaterally in the name of jihad and amr maâ€™ruf nahy munkar by creating destruction on the face of earth without clear opponents and objectives is not allowed in Islam. Instead, it is a social sin toward the ummah.